2006
DOI: 10.3147/jsfp.41.57
|View full text |Cite
|
Sign up to set email alerts
|

Serological Characterization of Streptococcus iniae Strains Isolated from Cultured Fish in Japan

Abstract: ABSTRACT-Streptococcus iniae is known as an important marine and freshwater fish pathogen worldwide. In this paper, we characterized two serological phenotypes in Japanese S. iniae isolates, mainly from Japanese flounder Paralichthys olivaceus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 49 publications
0
19
0
Order By: Relevance
“…They were routinely cultured using Todd-Hewitt agar or broth (Difco Laboratories) for 18 -24 h at 27∞C. FKC of each strain was prepared as described previously (Kanai et al, 2006).…”
Section: Bacteriamentioning
confidence: 99%
See 3 more Smart Citations
“…They were routinely cultured using Todd-Hewitt agar or broth (Difco Laboratories) for 18 -24 h at 27∞C. FKC of each strain was prepared as described previously (Kanai et al, 2006).…”
Section: Bacteriamentioning
confidence: 99%
“…Blood was collected from the residual five fish of each group and serum was separated from the blood by centrifugation at 900 ¥ g for 15 min. Agglutination titers of the sera were measured with FKC of S. iniae NUF631 and NUF44 (K -type) according to the previous paper (Kanai et al, 2006). Average water temperature during the vaccination period and after challenge was 25.5∞C and 26.3∞C, respectively.…”
Section: Vaccination Testmentioning
confidence: 99%
See 2 more Smart Citations
“…Kanai et al (2006) reported the presence and properties of two serological phenotypes, designated K + type and K -type, in Japanese S. iniae isolates, mainly from Japanese flounder. They showed that K + type exhibited a typespecific antigen and acidic polysaccharides in the autoclave-extracts of cells and a capsule on the cell surface, and that strains of K + type were virulent for Japanese flounder whereas those of K -type were avirulent.…”
mentioning
confidence: 99%